Persepsi Kerentanan Ibu Hamil terhadap Covid 19 Ditinjau dari Usia, Pendidikan dan Paritas: Persepsi Kerentanan Ibu Hamil terhadap Covid 19 Ditinjau dari Usia, Pendidikan dan Paritas - Dian Kusumaningtyas; Ratna Diana Fransiska; Kentri Anggarina Gumanti (Universitas Islam Jember, 2021)
Pregnant women are susceptible to health problems, especially infectious diseases due to changes in body physiology and immune response mechanisms in the body. The Health Belief Model theory states that a person will take action to prevent disease if they perceive themselves to be susceptible to a condition (perceived susceptibility). This study aims to determine the perception of the vulnerability of pregnant women to Covid-19 in terms of age, education and parity. The type of this research is an analytic study with a cross sectional approach. Research data obtained from primary data. it derived from questionnaires that given to 93 pregnant women from 5 public health centers in the area of ​​Malang City. The sampling technique of this study used accidental sampling. The results showed that there was no relationship between the age and parity of pregnant women and their perception of vulnerability during the Covid-19 pandemic (p=0,761; p=0,769) and there is a relationship between the education of pregnant women and the perception of their vulnerability during the Covid-19 pandemic (p=0.012). Many factors influence the perception of vulnerability of pregnant women, including education. Higher education will show wider knowledge of health conditions so that the higher the education of mothers, the faster they make decisions to prevent Covid-19. Meanwhile, the age and parity of pregnant women are not crucial factors that determine the perception of vulnerability of pregnant women during the pandemic, because all age and parity groups have the same possibility of being exposed to Covid-1 Keywords: perception of vulnerability, age, education, parity, covid-19